Challenging immateriality: Outline for a valuation model of invisible (and visible) heritage - Gomes, Ana Calapez (PASOS Revista de Turismo y Patrimonio Cultural, 2015)
<!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--><!--StartFragment--> The objective of this paper is the presentation of a valuation model for immaterial heritage, specially conceived for high mistrust and low communication contexts. The problematic of heritage valuation is closely linked with tourism, and immaterial heritage has been acquiring relevance in the process of cultural and creative tourism development. For its part, local harnessing of the benefits of tourism, namely in rural contexts, is very much dependent on the stakeholders’ capacity to organize themselves and cooperate in order to create valuable tourist experiences. The valuation model presented is built on a combination of former propositions (Lopes, 2012; Lupo, 2007; Saxena and Ilbery, 2008) and the preliminary results of a research project in the area of immaterial (partially invisible) heritage. <!--EndFragment-->